(untitled) (Research, Society and Development, 2020)
Considering the presence of novice nurses in the Intensive Care, requesting productivity and good performance; this study aims to describe how the insertion of a nurse for the Intensive Care Unit occurred; to identify the aspects that have influenced the permanent training in the context of his/her admission and post-admission at the Intensive Care Unit. 20 semistrucured interviews were conducted, worked on analysis content and Schon´s toughts. The categories lifted: the nurse in the course of a critical-reflexive learning; understanding the performance of another nurse; and developing his/her artistic professional talent as a leader in nursing. The nurses sought to bring back knowledge, used strategies for learning; observed the veteran´s performance; the embracement was a factor that eased the learning; infrastructure lacks related to the university hospital did not favored the learning; to be a leader and a beginner was a challenge faced by the nurses.